A Book Review: HOMING IN ON ONE'S RAGANG RINARANGA (BELOVED LAND) - Judith F. Balares Salamat (Soegijapranata Catholic University, 2007)
Ragang Rinaranga: Rawit-Dawit (roughly translate as Beloved Land: Poems) is the first published poetry book by Frank V. Penones Jr, a native of Iriga City, Philippines.